Respuesta :
[tex](5x+3)^2\\\\\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\=(5x)^2+2(5x)(3)+3^2\\\\=5^2x^2+30x+9\\\\=25x^2+30x+9\to D.[/tex]
Answer:
option D is correct
The result in standard form is,
[tex]25x^2+30x+9[/tex]
Step-by-step explanation:
The standard form of the equation is given by:
[tex]y = Ax^2+Bx+C[/tex] where, A, B and C are the coefficient and x is the variable.
Using the identity rule:
[tex](a+b)^2 = a^2+2ab+b^2[/tex]
Expand the expression:
[tex](5x+3)^2[/tex]
Apply the identity rule:
[tex](5x)^2+2(5x)(3)+3^2[/tex]
⇒[tex]25x^2+30x+9[/tex]
The result in standard form is, [tex]25x^2+30x+9[/tex]
Therefore, the result in standard form is, [tex]25x^2+30x+9[/tex]